Computational intelligence, cyber security and computational models : models and techniques for intelligent systems and automation : third International Conference, ICC3 2017, Coimbatore, India, December 14-16, 2017, Proceedings /: models and techniques for intelligent systems and automation : third International Conference, ICC3 2017, Coimbatore, India, December 14-16, 2017, Proceedings. (2018) - Unknown
No abstract available